A study of hill country development on Horowhenua sheep farms : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Agricultural Economics and Farm Management at Massey University - Halford, Ronald Edward (Massey University, 1971)
No abstract.
Keywords: Hill country farms; Sheep farming, Horowhenua, New Zealand; Farm management; Horowhenua farms